PENGEMBANGAN MODEL PERMAINAN TRADISIONAL EGRANG DALAM MENINGKATKAN MOTORIK KASAR ANAK USIA 3-4 TAHUN - Sitti Nurjannah; Muhammad Yusri; Abdulah Sinring; Herlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem in this study is how to develop a storytelling method through picture media. This development research aims to (1) find out How the need for the development of storytelling methods in improving children's reading literacy understanding (2) Researchers aim to find out How the prototype of The Development Of A Egrang Traditional Play Model In Improving Gross Motoric Of Children Aged 3-4 Years Old (3) Researchers aim to find out How the validity and practicality Egrang Traditional Play Model In Improving Gross Motoric Of Children Aged 3-4 Years Old This type of research is development research with Addie model research design. The data collection techniques used in this research are questionnaires, interviews, observation and documentation. The subjects in this study consisted of 2 teachers and 11 children of KB Rumah Qurani Imam Muslim Maros The data analysis techniques used were qualitative data analysis and quantitative data analysis. The results showed that (1) the description of the need for the development of Egrang Traditional Play Model In Improving Gross Motoric Of Children Aged 3-4 Years Old, (2) the design of the development of Egrang Traditional Play Model through image media is designed with a sequence of instrument preparation, namely: needs analysis, teacher response questionnaire, early childhood literacy level assessment, and (3) the level of validity and practicality of the development of Egrang Traditional Play Model the results of 3.38 with very valid criteria, and the practicality of the development of local cultural storytelling methods obtained the results of 89.45% with very valid criteria. While in effectiveness, the results obtained were 93.75% with the Highly Effective category. It can be concluded that the traditional game of stilts can improe the gross motor skills of children aged 3-4 years